Stimulation of Synaptic Vesicle Exocytosis by the Mental Disease Gene DISC1 is Mediated by N-Type Voltage-Gated Calcium Channels - Tang, Willcyn; Thevathasan, Jervis Vermal; Lin, Qingshu; Lim, Kim Buay; Kuroda, Keisuke; Kaibuchi, Kozo; Bilger, Marcel; Soong, Tuck Wah; Fivaz, Marc (Frontiers in Synaptic Neuroscience, 2016)
Lesions and mutations of the DISC1 (Disrupted-in-schizophrenia-1) gene have been linked to major depression, schizophrenia, bipolar disorder and autism, but the influence of DISC1 on synaptic transmission remains poorly understood. Using two independent genetic approaches – RNAi and a DISC1 KO mouse – we examined the impact of DISC1 on the synaptic vesicle (SV) cycle by population imaging of the synaptic tracer vGpH in hippocampal neurons. DISC1 loss-of-function resulted in a marked decrease in SV exocytic rates during neuronal stimulation and was associated with reduced Ca2+ transients at nerve terminals. Impaired SV release was efficiently rescued by elevation of extracellular Ca2+, hinting to a link between DISC1 and voltage-gated Ca2+ channels. Accordingly, blockade of N-type Cav2.2 channels mimics and occludes the effect of DISC1 inactivation on SV exocytosis, and overexpression of DISC1 in a heterologous system increases Cav2.2 currents. Collectively, these results show that DISC1-dependent enhancement of SV exocytosis is mediated by Cav2.2 and point to aberrant glutamate release as a probable endophenotype of major psychiatric disorders.